If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 19m + -1 = 8m + 106 + -2m Reorder the terms: 3 + -1 + 19m = 8m + 106 + -2m Combine like terms: 3 + -1 = 2 2 + 19m = 8m + 106 + -2m Reorder the terms: 2 + 19m = 106 + 8m + -2m Combine like terms: 8m + -2m = 6m 2 + 19m = 106 + 6m Solving 2 + 19m = 106 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 2 + 19m + -6m = 106 + 6m + -6m Combine like terms: 19m + -6m = 13m 2 + 13m = 106 + 6m + -6m Combine like terms: 6m + -6m = 0 2 + 13m = 106 + 0 2 + 13m = 106 Add '-2' to each side of the equation. 2 + -2 + 13m = 106 + -2 Combine like terms: 2 + -2 = 0 0 + 13m = 106 + -2 13m = 106 + -2 Combine like terms: 106 + -2 = 104 13m = 104 Divide each side by '13'. m = 8 Simplifying m = 8
| 3(2-3x)+x=10(x+2)-12 | | V^2+12v-44=-7 | | 9-2y=15 | | 3x-2=5x+17 | | 9y+5y=28 | | x+x=56 | | 15y+2+2Y-1= | | 9n^2-12n-17=7 | | += | | 48x^3-147x=0 | | 3059294+929582= | | 7+(-1)/(-18)=x | | 2x^2-12x+36=0 | | x=3n^2-5n+1 | | A+4.5=21.7 | | 9*-7=-7 | | y^2+18y+45=0 | | -4=4x/5 | | 65.7-t=24.9 | | 2(2b+2)+(5b-3)=0 | | -2y+4=-3(2y+4) | | 4s=2.8 | | 8x^2-50=23 | | 3(7x+7)=2x | | 0.9x-0.4x+4=-7 | | n+16=-9 | | I+9.3=15.6 | | 5x+25=8x+31 | | 7-(-1)/(-18)=x | | 5+3(4-2)=x | | 144x^2+384=0 | | 4.8q-4.8-5.8q=2.0q-3.6 |